Factors Affecting Customer Decisions To Save At Bank Mandiri Taspen Manna Branch Office Bengkulu Selatan - Marzan Marzan; Ahmad Soleh; Ida Ayu Made E. Gayatri (Journal of Indonesian Management, 2021)
The purpose of this study was to determine the effect of location, service quality and product quality on customer decisions to save at Bank Mandiri Taspen Sub-Branch Office Manna Bengkulu Selatan. The sample in this study was 100 customers who saved at Bank Mandiri Taspen, Manna Bengkulu Selatan Sub-Branch Office. The sampling technique is accidental sampling technique. The data was collected using a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. The results of multiple linear regression analysis show Y = 8.281 + 0.186X1 + 0.397 X2 + 0.235 X3 + e. Location has a significant influence on customer decisions to save at Bank Mandiri Taspen Sub-Branch Office Manna Bengkulu Selatan, this is evidenced by a significant value of 0.018 which is smaller than 0.05. Service quality has a significant influence on customer decisions to save at Bank Mandiri Taspen, Manna Bengkulu Selatan Sub-Branch Office, this is evidenced by a significant value of 0.000 which is smaller than 0.05. Product quality has a significant influence on customer decisions to save at Bank Mandiri Taspen, Manna Bengkulu Selatan Sub-Branch Office, this is evidenced by a significant value of 0.001 which is smaller than 0.05. Location, service quality and product quality jointly have a significant effect on customer decisions to save at Bank Mandiri Taspen Sub-Branch Office Manna Bengkulu Selatan, this is evidenced by a significant value of 0.000 which is smaller than 0.05.